Bridging Planning and Practice: Cognitive Assessment Based on Bloom's Taxonomy in Islamic Religious Education at Senior High Schools - Wulandari, Ayu; Anwar, Saepul; Faqihuddin, Achmad (Arfannur: Journal of Islamic Education, 2026)
This study investigates the pedagogical dissonance between curriculum expectations and classroom reality in the implementation of cognitive assessment within Islamic Religious Education (IRE). While existing literature highlights the gap between Higher-Order Thinking Skills (HOTS) planning and practice, a concise theoretical explanation for this divergence remains underexplored. Using an instrumental case study design involving IRE teachers at a senior high school in Bandung, this research deconstructs the assessment culture through in-depth interviews, observations, and document analysis. The study contributes to the literature by identifying two distinct, conflicting paradigms that govern assessment practices: the systematic–diagnostic paradigm, rooted in strict adherence to Bloom’s Taxonomy for formative improvement, and the contextual–summative paradigm, which prioritizes flexibility and social relevance for accountability. Theoretically, this research argues that the failure to institutionalize HOTS is not merely a technical competency issue but a result of the lack of integration between these two paradigms. The findings imply that fostering HOTS requires a "hybrid assessment model" that harmonizes systematic rigor with contextual adaptability, moving beyond the binary of diagnostic versus summative functions. This framework offers a novel lens for evaluating teacher competence in 21st-century religious education.